Propagation characteristics and control technology of blasting vibration in neighborhood tunnel - Qin, Zixiu; Zhao, Yihan; Chen, Lu; Cao, Hongtao; Zeng, Ling; Jiao, Wencan; Xu, Hong (Frontiers in Earth Science, 2023)
During the tunnel construction process using the drilling and blasting method, the induced blasting vibration always pose a great threat to the stability and safety of adjacent tunnel supporting structure. To improve the efficiency and safety of tunnel blasting construction, the vibration propagation and the peak particle velocity(PPV) distribution of the lining of excavated tunnel were investigated during blasting of adjacent tunnel located at the Guangxi province. The evolution process and distribution characteristics of the PPV of the lining of adjacent tunnels were monitored and analyzed. The results show that the maximum blasting vibration velocity of the lining of the adjacent tunnel can be shown as: PPVx > PPVz > PPVy, hence the PPVx plays a significant role in the vibration of the adjacent tunnel.According to the tensile stress failure criterion, the PPV threshold is determined to be 12.7 cm/s in this study. To control the damage of surrounding rock induced by the blasting vibration, the compound wedge-shaped cutting technology, the stress wave dislocation superposition technology and pre-splitting blasting technology are performed to reduce the impact of blasting vibration on the excavated tunnel.